The impact of employee performance on the quality of Hajj pilgrim services: A study at the Ministry of Religious Affairs - Deria, Monica Desi; Izmuddin, Iiz (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
This study investigates the influence of employee performance on the quality of Hajj services at the Ministry of Religious Affairs in Pasaman Regency. The research aims to develop a comprehensive model linking employee performance indicators (quality of work, communication, promptness, capability, and initiative) to service quality dimensions (responsiveness, assurance, tangibles, empathy, and reliability). Employing a quantitative approach, primary data were collected from 92 respondents using simple random sampling, and analyzed through validity and reliability tests, linear regression, and hypothesis testing. The results indicate a significant positive relationship between employee performance and service quality, with a regression coefficient of 0.804 and an R² value of 0.705, implying that 70.5% of the variance in service quality is explained by employee performance. The findings suggest that enhancing employee performance can substantially improve the quality of Hajj services, providing actionable insights for the Ministry to implement targeted human resource practices. Future research should extend this analysis to other regions and explore additional variables influencing service quality in the Hajj context.